Building information research skills in the Pacific region: The University of the South Pacific Initiative. Issue 3 (10th January 2019) - Alenzuela, Reysa; Fong, Elizabeth; Bloss, Jamie; Chambers, Vasiti
Abstract : Purpose: Information literacy (IL) enables individuals to discover new ways of thinking and new knowledge across a range of platforms, tools and media. It hopes to enable them to fit into the world of research and scholarly communication. This paper aims to describe the development and current practices in IL program at the University of the South Pacific (USP). This case study puts emphasis on how IL at USP reflects the educational priorities of the University and the region. Discussions on socio-cultural context hope to provide insights on developing a framework based on global standards that address the cultural aspect within students' learning environment in the 12 member countries. Design/methodology/approach: This paper mainly used desktop research and document analysis to present the IL model which is cohesively embedded within the University's strategic plan and research skills development framework. Findings: The results are summarized in three sections: paradigms and models as basis, current content and mode of delivery, methodologies and design for instruction and socio-cultural insights. Research limitations/implications: At present, this study will cover Fiji (the Main Campus) and Vanuatu (School of Law). Other member countries with USP presence such as Cook Islands, Kiribati, Marshall Islands, Nauru, Niue, Samoa, Solomon Islands, Tokelau, Tonga and Tuvalu are considered as part of the future design. Ultimately, a comprehensive model that is applicable for 21 other campuses in the ten member countries will be designed. It also hopes to be replicable in the entire Pacific context. Practical implications: This study provides baseline data to develop future strategies for implementation in the regional level. Originality/value: This paper deals with definitional issues of IL related to Pacific cultural contexts that goes beyond a single country, one national identity as it deals with 11 countries, a different model for networked paradigm for IL.